Different origin-derived exosomes and their clinical advantages in cancer therapy - Jin, Xiaoyan; Zhang, Jing; Zhang, Yufu; He, Jing; Wang, Mingming; Hei, Yu; Guo, Shutong; Xu, Xiangrong; Liu, Yusi (Frontiers in Immunology, 2024)
Exosomes, as a class of small extracellular vesicles closely related to the biological behavior of various types of tumors, are currently attracting research attention in cancer diagnosis and treatment.Regarding cancer diagnosis, the stability of their membrane structure and their wide distribution in body fluids render exosomes promising biomarkers. It is expected that exosome-based liquid biopsy will become an important tool for tumor diagnosis in the future. For cancer treatment, exosomes, as the "golden communicators" between cells, can be designed to deliver different drugs, aiming to achieve low-toxicity and low-immunogenicity targeted delivery. Signaling pathways related to exosome contents can also be used for safer and more effective immunotherapy against tumors.Exosomes are derived from a wide range of sources, and exhibit different biological characteristics as well as clinical application advantages in different cancer therapies. In this review, we analyzed the main sources of exosomes that have great potential and broad prospects in cancer diagnosis and therapy. Moreover, we compared their therapeutic advantages, providing new ideas for the clinical application of exosomes.